Kualitas Pelayanan Fiskus Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor Pada Samsat Jakarta Timur - Simanjuntak, Gilbert Billy Dionisius; Maruli, Riky Sai; Susanti, Mila (Program Studi Magister Manajemen Universitas Advent Indonesia, 2024)
Abstract This research aims to test motor vehicle taxpayer compliance by testing the quality of tax services provided by tax authorities to assist taxpayers in planning and managing their tax obligation needs at SAMSAT East Jakarta. This research uses a quantitative method using 64 primary sample data collected by distributing questionnaires to motor vehicle taxpayers at SAMSAT, East Jakarta. The research conducted hypothesis testing using multiple linear regression with the SPSS version 25.0 application. The results of the research show that the quality of tax service has a significant positive effect on motor vehicle taxpayer compliance. In other words, motor vehicle taxpayer compliance is determined by the quality of tax service to taxpayers.